2012
DOI: 10.1080/17458080.2012.678393
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of magnetic nanoparticles in a pH-sensitive poly(4-vinyl pyridine) polymer: a step forward to a multi-responsive system

Abstract: A multiresponsive system that consists on pH-responsive polymer microspheres with encapsulated iron oxide magnetic nanoparticles that rendered the core magnetic to enable externally controlled actuation under magnetic induction has been developed. The inorganic nanoparticles were first prepared and, then, further encapsulated in a pH-sensitive poly(4-vinylpyridine). These spheres have been obtained by a modification of the simple, rapid and high-reproducible nanoprecipitation method. Magnetic measurements show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The physicochemical principles of non-protein NP synthesis using nanoprecipitation, such as the mixing steps and the solvents, have been thoughtfully investigated. 94 Moreover, the path to industrialisation has also been explored, such as modifications on an industrial scale and the establishment of controlled microfluidic systems. [95][96][97] Therefore, this method is considered to have a high expectation for BD encapsulation due to its simplicity of operation and its ability to avoid exposure to different emulsifiers and surfactants under sonication conditions.…”
Section: Nanoprecipitationmentioning
confidence: 99%
“…The physicochemical principles of non-protein NP synthesis using nanoprecipitation, such as the mixing steps and the solvents, have been thoughtfully investigated. 94 Moreover, the path to industrialisation has also been explored, such as modifications on an industrial scale and the establishment of controlled microfluidic systems. [95][96][97] Therefore, this method is considered to have a high expectation for BD encapsulation due to its simplicity of operation and its ability to avoid exposure to different emulsifiers and surfactants under sonication conditions.…”
Section: Nanoprecipitationmentioning
confidence: 99%
“…Nevertheless, some interesting developments of nanoparticles prepared by nanoprecipitation have been reported as well. For example, Arizaga et al [39] and Villela et al [40] entrapped magnetic nanoparticles inside polymeric particles, Fan et al [41] designed spatially controlled release multistage carriers via the complexation of dendrimers with gelatin, and Allen et al [35] entrapped hydrophobic and hydrophilic active molecules into polymersomes. Likewise, modifications to facilitate the industrial scaling-up of the preparation process have been investigated by Charcosset et al [42] and D'Oria et al [43] who developed procedures based on the use of a membrane contactor.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25][26][27] Moreover, it has been reported that polymers functionalized with nanoparticles containing pyridine groups can be used in technological applications such as absorption and conversion of CO 2 , homogeneous catalysis, pH sensors, opto-biodetection and biomedical applications, among others. [28][29][30][31][32] Considering these backgrounds, in this work we report the synthesis, characterization and preparation of films from a series of soluble aromatic copolyimides derived from 4,4'-(hexafluoroisopropylidene)diphtalic anhydride (6FDA), 4,4'-oxydianiline (ODA) and the new diamine 3,5-diamino-N-(pyridin-4-ylmethyl)benzamide (PyDA). These polymers have imide groups which provide both thermal and mechanical stability, partially incorporate a pendant pyridinyl group that will allow functionalization with several nanoparticles in the future, as well as the presence of amide groups that may facilitate water permeability through the membrane.…”
Section: Introductionmentioning
confidence: 99%